Medication management tips to stay healthy and happy this Eid / Hasryn Azzuar Mohd Khairy - Mohd Khairy, Hasryn Azzuar (Faculty of Pharmacy, 2023)
There is no problem with travelling long distances while taking medication continuously, as long as the rules of taking medication are always followed. Long trips may be harmful if medication is not taken properly, especially for chronic patients. Here are some tips on medication safety during the festive season and long journeys. If you need to take medication, such as antihistamines, that can affect driving (by causing drowsiness), you need to adjust the time you take it. Such medication is advised to be taken at night to make it easier for you to sleep and get enough rest so that driving back during the day will be smoother.